YOUNG PEOPLE’S PERCEPTION OF DIGITAL TRANSFORMATION - Hariwibowo, Ignatius Novianto (LATTE: A Journal of Language, Culture, and Technology ISSN 3063-0754, 2025)
This study aims to explain young people's perception of digital changes that are increasingly massive. This study is important to provide clarity on the readiness of young people, namely students in higher education, to face the challenges of the digital era. This study uses a descriptive approach with a sentiment analysis method. This approach was chosen because it can capture the perception of young people naturally. The respondents in this study were 440 students from various educational backgrounds. Respondents responded by answering open-ended questions submitted through google forms. The results show that the majority of respondents have positive sentiments towards the digital transformation that is taking place. Mayoitas of respondents also showed readiness to enter digital transformation. These findings show that young people can accept and are ready to enter the digital transformation. The findings emphasize the identification of patterns that higher understanding is not always proportional to positive sentiment, but rather encourages critical and reflective attitudes. These findings enrich the literature that has so far highlighted the linear relationship between digital literacy and positive attitudes towards digital transformation.